ASPECTOS PALEOECOLOGICOS DE LOS FORAMINIFEROS DEL CRETACICO DE LA CUENCA AUSTRAL (Ameghiniana, 2013)
The Cretaceous foraminiferal faunas of the Austral Basin, of temperate-cold water, show a strong control-facies which is responsible for the high percentage of agglutinated foraminifers. The main paleoecological features of local sta.je faunas are: the Esperanzian fauna (Hauterivian-Valanginian) represents a shelf fauna of a landlocked sea with anaerobic bottom conditions. In the following stages Jt is possible to differentiate two areas, one dominated by agglutinated foraminifers typical of flysch, flysch-like and associated sediments fron he Cordilleran part, and on the other hand, microfaunas of the stable shelf of the basin, are dominated by calcareous forarninifers with a rather high and variable content of agglutinated forms. The main characteristic of the Tenerifian faunas (Aptian-Albian) -frequent planktonics (Foraminifera, Radiolaria and Calcareous Nannoplankton) and poor developed benthonic foraminifers faunas- is probably due to the persistence of anaerobic bottom conditions. From the Peninsulian (Cenomanian) up to the Lazian, the benthonic faunas are more diversified in the shelf area, while in the geosynclinal are a typical benthonic assemblages of flysch and associate 'environments occurs. In the Lazian the molassic regimen in the northern part of fue basin with a fauna dominated by Spiroplectammina and Textularia, representing the final withdrawal of the Cretaceous sea, which at the end of that time extended almost over all the basin takes place. Throughout the Cretaceous the planktonic foraminifera, of typical austral character, are very similar to those know n from the Boreal Province.